The Employability Skills Among Vocational School Students in the Final Year of Malaysian Skills Certificate - Norzaina Rasit; Mohd Mokhtar Tahar (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2018)
Birth of highly-paid generation can happen through a vocational education system that emphasizes on comprehensive vocational training in addition to ample knowledge, immense skills, globally acknowledged certificate and strong employability skills. Thus, this study is done to identify the level of employability of students with disability whom already went through the training process. This study is also done to determine the difference between the level of employability skills between the gender of students as well as their specialty in their respective areas. This descriptive and quantitative study includes 60 students of Sekolah Menengah Pendidikan Khas Vokasional Indahpura who are in their final year of studying the Malaysian Skills Certificate. One set of questionnaire is adapted from the Employability Skills Model which is used as an instrument to analyze the statistics such as the frequency, mean score, standard deviation, T-Test and One-way ANOVA by using a computer programme known as Statistical Package for Social Science (SPSS). The result shows that the employability skills of the student are on the medium level. There are no coexistence differences proven between the level of employability skills with the gender of the students as well as none with the areas that they are specialized in. It is hoped that the analysis of the sample that had been used in this study will be used as guidance to improve the implementation of employability skills as well as teaching and learning process in Vocational school.